PENGARUH CUSTOMER EXPERIENCE TERHADAP REPURCHASE INTENTION TAMU DI SWISS-CAFE RESTAURANT LAMPUNG - Desinda Ayu Putri; Rendy Sarudin (LPPM Institut Pendidikan Nusantara Global, 2023)
The main purpose of this research is to confirm the relationship between Customer Experience and Repurchase intention in Swiss-Café Restaurant Lampung. The analytical method used in this research includes Mean descriptive statistics analysis, classical assumption test, simple linear regression, and hypothesis test. The result gathered from t test shows significancy score of 0,000 < 0,05 and the t count 15,617 > t tabel 1.98447 which means that there is a significant effect of Customer Experience on Repurchase intention. R2 with a value of 0,713 Means that the influence from variable X towards variable Y is 71.3% with the remainder being influenced from other factors outside of the scope of this research.